PRINSIP-PRINSIP MANAJEMEN KESISWAAN DALAM TINJAUAN AL-QURAN - Muhammad Alimi; M.arya rasidi; Syafaatul Habib (As-Sulthan Journal of Education, 2025)
Planning, directing, implementing and supervising student activities at school is part of student management, which aims to create a learning environment that supports overall student growth. Including achievement assessments, extracurricular activities, and character development. In addition to providing a living environment that supports students' development into morally mature and responsible human beings, the goal is to ensure students' growth in academic, social and emotional areas. The rivew literature review process was used in the review of this research article. This process organizes the resources needed to write a research proposal based on research findings and helps in categorizing the current body of literature into relevant subjects. In this case it is intended that by monitoring students' reading of the hadith and Al-Quran, everyone can help them in achieving their academic goals. Character development, equity, lifelong learning, and a supportive learning environment are some of these ideals. Al-Qur'an verses, such as QS. An-Nahl verse 125, emphasizes the importance of disseminating information wisely and participating in productive debates